The Ecology Character Of Banda Aceh City In The 17th Century - Wulandari, Elysa; Soetomo, Sugiono; Syahbana, Joesron Alie; Manaf, Asnawi (Journal of Islamic Architecture, 2017)
Bandar Aceh Darussalam as tamaddun city in the tip of Sumatera Island and capital city of 17th century Islamic Aceh Sultanate, was a strategic coastal city. It had sloping beach and bays and was surrounded by mountains with rivers flowing through the city. Its wetlands-based urban development was reflected in the design of urban space structure and key elements of the city. It becomes inspiration for developing modern ecological city since 17th century Islamic cities in archipelago of the East is rarely studied. This research aimed to study the spatial concept of Bandar Aceh Darussalam. Data was collected by using the method of tracking physical information through ancient maps and field observation of the environment characteristic. It was found that the ecological character of the city seemed to be affected by the existence of integrated natural features, function and the role of the city that included Islamic concepts. The main elements of the city reflected the character of civilization in three aspects: the drainage system i.e. cut and fill, the scattered and wide empty space, and natural defense system. The concept of harmony between urban development and city’s ecological character was shown in the design of urban landscape.